2017
DOI: 10.1177/0898010117736686
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well-Being, Depression, and Stress Among Hemodialysis Patients in Jordan

Abstract: 00962 2 6297052.The authors declare that there are no conflicts of interest. AcknowledgementsThis research was kindly funded by Al al-Bayt University (a Jordanian governmental university) and this funding will not pose conflict of interest. AbstractPurpose: The spiritual dimension of a patient's life is an important factor that may mediate detrimental impacts on mental health. The lack of research investigating spiritual wellbeing, religiosity, and mental health among Jordanian hemodialysis patients encouraged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
55
2
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 26 publications
7
55
2
13
Order By: Relevance
“…The positive effects of religion extend beyond Christianity. A study of patients receiving hemodialysis in Jordan discovered that the more religious Muslims were, the less likely they reported depressive symptoms (Musa et al 2018). Researchers found that spiritual wellness practices such as fasting, prayer, fostering positive relationships, expressing beliefs through art, and studying religious materials served as protective factors against depression.…”
Section: Religiosity and Adolescent Depressionmentioning
confidence: 99%
“…The positive effects of religion extend beyond Christianity. A study of patients receiving hemodialysis in Jordan discovered that the more religious Muslims were, the less likely they reported depressive symptoms (Musa et al 2018). Researchers found that spiritual wellness practices such as fasting, prayer, fostering positive relationships, expressing beliefs through art, and studying religious materials served as protective factors against depression.…”
Section: Religiosity and Adolescent Depressionmentioning
confidence: 99%
“…There are many studies on the treatment-related stressors experienced and coping strategies used by patients on HD [2,[8][9][10][11][12]. In Tu et al [8]'s study, Taiwanese patients on HD aged 20-45 years were found to have high stress levels.…”
mentioning
confidence: 99%
“…On the other hand, in Parvan et al [9]'s study, most Iranian patients on HD reported using emotion-focused coping strategies more than problem-focused strategies. In a recent cross-sectional study of 218 Jordanian patients on HD, Musa et al [10] reported that patients demonstrated mild to moderate stress. The investigators have also showed that patients on HD used religious and spiritual beliefs as coping strategies to overcome their stress [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations